The Effectiveness of Management Information System (MIS) Digitalization in Transforming Administrative Governance at Pondok Pesantren Minhajul Haq Purwakarta - Isrun Abdurahman; Rahman Pranoto; Irfan Alkhotiri; Rizaldy Alpiansyah (Labina : Journal of Islamic Education Management, 2026)
Administrative digitalization is a fundamental pillar in the modernization of Islamic educational institutions in the Society 5.0 era. This study aims to analyze the effectiveness of implementing an integrated Management Information System (MIS) at Pondok Pesantren Minhajul Haq Purwakarta. The scope of the research includes the transformation of governance in the New Student Admissions (PPDB) sector, integrated attendance systems (teachers, students, and halaqoh), administrative correspondence (TU), and library automation. Using a descriptive qualitative approach with a single case study, data collection was conducted over six months involving 45 informants, system observation, and server log analysis. The results showed that the implementation of the MIS successfully reduced PPDB administrative processing time from an average of 144 hours to 1.2 hours. Furthermore, the GPS-based geofencing attendance system increased educator discipline to 98.7%, while the paperless E-Office policy reallocated IDR 41,700,000 of the annual logistics budget to cloud infrastructure development. The transparency of academic and memorization data (ziyadah) accessed via the mobile application significantly increased parental engagement. In conclusion, digitalization at Pondok Pesantren Minhajul Haq does not reduce traditional salaf values but strengthens institutional accountability, transparency, and competitive advantage.